2013
DOI: 10.1017/s1368980013001626
|View full text |Cite
|
Sign up to set email alerts
|

Public health policy to redress iodine insufficiency in pregnant women may widen sociodemographic disparities

Abstract: Objective: To evaluate the impact of a mandatory bread fortification programme on estimated iodine intakes of childbearing women and to describe the extent to which uptake of a maternal iodine supplement recommendation is associated with sociodemographic characteristics. Design: A postpartum survey was conducted using a self-administered questionnaire. Details on pre-and post-conceptional supplement use, bread intake, iodized salt use and maternal sociodemographic and obstetric characteristics were obtained. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…We estimated an increase in iodine intake of approximately 31 μg/day from bread reflecting an average consumption of 2 slices per day. This is comparable to the estimated post-fortification increase of iodine intake from bread, of 35 to 37 μg/day in women of childbearing age [14] and in adults aged 18 to 64 years [8], but lower than the modeled estimate of 52 μg/day in children [4]. …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We estimated an increase in iodine intake of approximately 31 μg/day from bread reflecting an average consumption of 2 slices per day. This is comparable to the estimated post-fortification increase of iodine intake from bread, of 35 to 37 μg/day in women of childbearing age [14] and in adults aged 18 to 64 years [8], but lower than the modeled estimate of 52 μg/day in children [4]. …”
Section: Discussionsupporting
confidence: 67%
“…For example, older institutionalized adults with renal insufficiency may have lower iodine requirements from decreased excretion of iodine. Therefore, while previous studies have focused on monitoring the effect of the mandatory bread fortification program on the iodine intake or status of younger populations [9,14], it is also important to evaluate the impact of the program on the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…However, UIC in the current study (65 µg/l) represents an increment of only 25% (13 µg/day) compared to the median UIC (52 µg/l) of women in a national study prior to iodine fortification [26]. Although, the estimated iodine intake (130 µg/day) in the present study was twice the intake estimated for women prior to fortification (63 µg/day) in the 2009 New Zealand Total Diet Survey (NZTDS) [29], their urinary iodine status still classified them as iodine-deficient. In addition, the estimated median intake is below the EAR of 160 and 190 µg/day for pregnant and lactating women respectively, thus they would remain at risk of inadequate iodine intake if they became pregnant, despite mandatory fortification.…”
Section: Open Access Fnsmentioning
confidence: 65%
“…It is therefore essential that pregnant and lactating women use the subsidised iodine supplement to ensure sufficient iodine intake during this time. However, a recent observational study in NZ (n = 723) reported low use of iodine containing supplements among pregnant women, especially low income women [29].…”
Section: Open Access Fnsmentioning
confidence: 98%
“…While the etiology of the observed disparities have not been fully elucidated [55], evolving research has begun to focus on prenatal maternal nutritional status [36, 39] with a few studies documenting sociodemographic disparities in both dietary and supplement intakes in pregnant women and women of child-bearing age [15, 18]. Methods are needed among pregnant minorities in order to ensure the success of accurately measuring prenatal intake.…”
Section: Introductionmentioning
confidence: 99%